2009
DOI: 10.1021/jm900968s
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Disrupting Activity of Tubulin-Binding 1,5-Diaryl-1H-imidazoles

Abstract: Highly cytotoxic 1,5-diaryl-1H-imidazoles were studied to clarify the relationship between cytotoxicity and activity as vascular disrupting agents (VDA). All the compounds disorganized the tubulin cytoskeleton, affected endothelial cell morphology and capillary formation in vitro, and caused vessel shutdown and tumor necrosis in vivo, thus confirming their vascular disrupting properties. Nonetheless, the substitution patterns on the imidazole ring, responsible for greater interaction energy with tubulin and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…Morphological changes to endothelial cells after treatment with VDAs, including membrane blebbing, have been observed in both in vitro and in vivo studies (Kanthou and Tozer, 2002;Yeung et al, 2007;Bonezzi et al, 2009), and the rounding-up and blebbing clearly apparent in HUVEC exposed to CYT997 (Fig. 1) are thus fully consistent with these literature data.…”
Section: Discussionsupporting
confidence: 87%
“…Morphological changes to endothelial cells after treatment with VDAs, including membrane blebbing, have been observed in both in vitro and in vivo studies (Kanthou and Tozer, 2002;Yeung et al, 2007;Bonezzi et al, 2009), and the rounding-up and blebbing clearly apparent in HUVEC exposed to CYT997 (Fig. 1) are thus fully consistent with these literature data.…”
Section: Discussionsupporting
confidence: 87%
“…The rationale of the design of active compounds was to retain the appropriate geometry of the two adjacent aryl groups required for potent bioactivity of chemically stable cis-restricted derivatives of CA-4. These were obtained by incorporating the olefinic double bond into vicinally diaryl-substituted fivemember aromatic heterocyclic rings (Table 1), such as pyrazole [67], imidazole [67][68][69], thiazole [70][71][72], furazan (1,2,5-oxadiazole) [73], furan [74,75], thiophene [76,77], isoxazole [78,79], oxazole [67,68,80,81], 1,2,3-thiadiazole [39], triazole [82,83,84,85], 1,2,3,4-tetrazole [70,86] and dioxolane [87]. Replacement of the olefinic bond with a five-member heterocyclic ring allowed the retention of the correct geometric orientation of the two phenyl rings of CA-4, placing them at an appropriate distance for efficient interaction with the colchicine-binding domain on tubulin [35].…”
Section: Other Synthetic Stilbene Derivatives As Tubulin-interactive mentioning
confidence: 99%
“…Generally, introduction of N-containing 5-membered heterocycles as linkers between two aryl rings in CA4 analogues (Figure 1, III) resulted in potent cytotoxic compounds with antimitotic microtubule destabilizing mode of action. [11][12][13][14][15][16][17][18][19][20] Similarly, CA4 analogues with bicyclic triazolopyrimidine linker, halogen substituted triazolopyrimidines (Figure 1, IV), displayed cytotoxicity against human cancer cell lines with IC50 in nanomolar concentration range. 21 In the present study, polymethoxyhydroxy-substituted diaryltriazolopyrimidines 9 were found to be inactive up to 4 microMol concentration.…”
Section: Page 158mentioning
confidence: 99%
“…Spontaneous isomerization to the trans-double bond observed both in vitro and in vivo causes a dramatic decrease of biological activity. 10 To stabilize the active cis-conformation, several heteroaromatic rings, such as pyrazole, 11 imidazole, 11,12 thiazole, 11 isoxazole, 13,14 1,2,3-thiadiazole, 15 isomeric triazoles, 11,16,17 and tetrazole 11,[18][19][20] have been introduced as a nonisomerizable and metabolically stable isosteric equivalent of cis-double bond (Figure 1, III), resulting in highly active microtubule destabilizing antimitotic agents. Replacement of the double bond by triazolopyrimidine yielded diaryl-o-substituted-triazolopyrimidines (Figure 1, IV) with pronounced cytotoxicity against human cancer cells both in vitro and in mouse xenograft model.…”
Section: Introductionmentioning
confidence: 99%